Pumpkin and watermelon production constraints and management practices in Uganda - Fred B. Masika; Titus Alicai; Hussein Shimelis; Gabriel Ddamulira; Shahasi Y. Athman; Perpetua Ipulet; Morgan Andama; Arthur K. Tugume (CABI Agriculture and Bioscience)
Abstract Background Watermelons and pumpkins are cultivated in Uganda for their leaves, fruits, and seeds, thereby contributing to food, nutrition and income security. However, there is limited research and information on constraints affecting their production. This study assessed the current production constraints for watermelons and pumpkins, management practices, sources of production inputs to guide research and decision making in production of these crops. Methodology Watermelon and pumpkin fields totalling 105 located in 28 districts from nine sub-regions of Uganda were surveyed. Purposive sampling was conducted based on the importance and availability of watermelon and pumpkin fields in the sub-regions using a questionnaire administered to farmers on different practices, management strategies, and current production constraints. Data were analysed to determine the relationship between the source of seed, sale of their produce, constraints, and control measures of biotic constraints in the different sub-regions. Results Pumpkins and watermelons were grown by 85.7% and 14.3% of respondent farmers, respectively. The constraints as ranked by the farmers were pests, diseases, drought, high transport and labour costs. Bacterial wilt, downy mildews, anthracnose powdery mildews and virus diseases in this order were the most common and important disease constraints. The whitefly (Bemisia tabaci, Gennadius), order hemiptera family aleyrodidae, aphids (Myzus Persicae, Sulzer), order hemiptera family aphidadae, melon fly (Bactrocera cucurbitae, Coquillett), order diptera family tephritidae and cutworm (Agrotis ipsilon, Hufnagel), order lepidoptera family noctuidae, were reported as the most limiting pests of watermelon and pumpkin production. Mixing of several agrochemicals was observed in watermelon fields coupled with gross lack of knowledge of proper usage or purpose of these chemicals may result in pesticide resistance, health and environmental hazards. Conclusion Pests, diseases, and drought constitute the main constraints affecting watermelon and pumpkin cultivation in Uganda. Whereas weeding using hand hoes is the most common method of weed control, application of ash was the main strategy for pest management in pumpkin, while in watermelons, pheromone traps and pesticides were frequently used.